Highly sensitive and selective acute myocardial infarction detection using aptamer‐tethered MoS2 nanoflower and screen‐printed electrodes. (2nd November 2020) - Vasudevan, Mugashini; Tai, Melvin J.Y.; Perumal, Veeradasan; Gopinath, Subash C.B.; Murthe, Satisvar Sundera; Ovinis, Mark; Mohamed, Norani Muti; Joshi, Nirav
Abstract: Acute myocardial infarction (AMI) is one of the leading causes of death worldwide. Cardiac troponin I (cTn1) is a commonly used biomarker for the diagnosis of AMI. Although there are various detection methods for the rapid detection of cTn1 such as optical, electrochemical, and acoustic techniques, electrochemical aptasensing techniques are commonly used because of their ease of handling, portability, and compactness. In this study, an electrochemical cTn1 biosensor, MoS2 nanoflowers on screen‐printed electrodes assisted by aptamer, was synthesized using hydrothermal technique. Field emission scanning electron microscopy revealed distinct 2D nanosheets and jagged flower‐like 3D MoS2 nanoflower structure, with X‐ray diffraction analysis revealing well‐stacked MoS2  layers. Voltammetry aptasensing of cTn1 ranges from 10 fM to 1 nM, with a detection limit at 10 fM and a sensitivity of 0.10 nA µM −1  cm −2 . This is a ∼fivefold improvement in selectivity compared with the other proteins and human serum. This novel aptasensor retained 90% of its biosensing activity after 6 weeks with a 4.3% RSD and is a promising high‐performance biosensor for detecting cTn1. Abstract : An illustration of overall surface modified (layer by layer) SPE to capture Troponin I by Aptamer together with supported Troponin I concentrationS and I‐V measurements (surface modification) results.